Creating a high quality consultant led psychiatric intensive care unit multidisciplinary team ward round. (25th March 2013) - Curtis, Peter; Sethi, Faisil; Ahmed, Farhana
Abstract Ward round is an integral platform for patients and the multidisciplinary team to communicate, assess and plan treatment. With such a key process, it is vital that the effectiveness of the ward round is maximised and that reliable follow of information is addressed. This can be achieved using lean methodology. Aim : To improve the quality of ward rounds, particularly reliability and patient experience. Method : This is a quantitative quality improvement study that used a plan-do-study-act cycle, including process mapping. The improvements were measured by an objective patient survey, staff survey and a checklist. Results : Process mapping identified the use of templates for the ward round plan, nursing and medical summaries. There was an increase in the reliability of ward round relating to flow of information measured by the checklist. Patient experience improved, rated by both patient and staff surveys, after series of changes were put in place. Conclusions : Checklists in the form of templates improved the reliability of information flow for patient treatment. If the multidisciplinary team is clear about what information and tasks are necessary, there will be a more reliable assessment. With the implementation of the plan template, more treatment plans are fully comprehensive enabling the consistent delivery of high quality of care.